An Evaluation of the Smart School Teacher Training Programme and its Impact on Integrating Technology into Teaching and Learning Processes in Malaysia - Ibrahim, Mohammed Sani (SOSIOHUMANIKA, 2009)
ABSTRACT: The aim of this study was to evaluate the effectiveness of conducting the 14 weeks In-Service (INSET) Course for the training of Smart School teachers, which was conducted by the Teacher Education Division, Ministry of Education, Malaysia and the In-House Training at the school levels. Questionnaires were administered to a total of 882 teachers and 2,689 students from 70 Smart Schools in Malaysia. The main findings from this study showed that teachers who had attended the courses had acquired all aspects of Smart School teaching and learning strategies which comprised of acquiring the concept, planning the Smart teaching, the Smart School teaching and learning processes, management of Smart classes except the Smart School assessment and evaluation techniques. In implementing the Smart School programme at their respective schools, teachers were facing numerous constraints which included heavy work load, insufficient funds, examination forces, time management, syllabi demands, empowerment aspect, receiving different directives from different superiors, studentsâ factors, inadequate help from colleagues and supports from their superiors. In spite of that, 82.8% of the respondents admitted that they still implemented the Smart School programmes and conducted In-House trainings for other teachers at their respective schools. Key words: smart school, teacher training programme, in-house training, and teachersâ competences in Malaysia.About the Author: Dr. Mohammed Sani Ibrahim is currently a Lecturer in the Faculty of Education UKM (National University of Malaysia). For academic purposes, he can be contacted at: inas_miharbi@yahoo.comHow to cite this article? Ibrahim, Mohammed Sani. (2009). âAn Evaluation of the Smart School Teacher Training Programme and its Impact on Integrating Technology into Teaching and Learning Processes in Malaysiaâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.2, No.2 [November], pp.253-280. Bandung, Indonesia: Minda Masagi Press, UNIPA Surabaya, and UMS Kota Kinabalu, Malaysia, ISSN 1979-0112. Chronicle of article: Accepted (September 20, 2009); Revised (October 23, 2009); and Published (November 20, 2009). Â Â